1998
DOI: 10.1021/js980222j
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Pluronic F127-Based Sustained-Release Ocular Delivery Systems for Pilocarpine using the Albino Rabbit Eye Model

Abstract: The overall objective of this study was to develop Pluronic F127 (PF127)-containing formulations of pilocarpine hydrochloride (PHCL) which can be used for sustained-release ocular delivery of PHCL. The PF127 formulations of PHCL containing methylcellulose (MC) or hydroxypropyl methylcellulose (HPMC) as an additive had previously exhibited the slowest dissolution rates and released the drug the slowest in vitro. This study was performed to assess the in vivo performance of these two formulations using miosis in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
34
0
1

Year Published

2003
2003
2014
2014

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 67 publications
(38 citation statements)
references
References 24 publications
3
34
0
1
Order By: Relevance
“…The BF1 and BF4 formulations presented surface tension values of 38-39 mN m À1 at 348C (the temperature of the ocular surface), 23 which are similar to those of normal tears (40-50 mN m À1 ). 34 No ocular damage or clinically abnormal signs were observed in the cornea, conjunctiva or iris. Only grades 0 and occasionally 1 were recorded, and no differences between the control and treated eyes for each group of rabbits were observed.…”
Section: Ocular Bioavailabilitymentioning
confidence: 91%
“…The BF1 and BF4 formulations presented surface tension values of 38-39 mN m À1 at 348C (the temperature of the ocular surface), 23 which are similar to those of normal tears (40-50 mN m À1 ). 34 No ocular damage or clinically abnormal signs were observed in the cornea, conjunctiva or iris. Only grades 0 and occasionally 1 were recorded, and no differences between the control and treated eyes for each group of rabbits were observed.…”
Section: Ocular Bioavailabilitymentioning
confidence: 91%
“…The reduction of the volume (e.g., 20 ml instead of 60Y100 ml) administrated in the eyes generally improved the AUC. Indeed, limitation of reflex tearing reduces lachrymal drainage and thus favours drug residence in the pre-ocular structure (82).…”
Section: Ophthalmic Formulationmentioning
confidence: 99%
“…9 The combination of Poloxamer-407 and HPMC provides a drug delivery matrix with slower drug release compared to either component alone. 10,21,25,26 In the present studies, we examined the mobilization properties of Flt3L when formulated in a sustained release matrix composed of Poloxamer-407 and HPMC. Our pharmacokinetic analyses demonstrated that the administration of Flt3L formulated with PG (PG-Flt3L) resulted in sustained delivery.…”
mentioning
confidence: 99%